Lesions characteristic of infection or malignant tumor in Paleo-Eskimo skulls - Lagier, René; Baud, Charles-Albert; Arnaud, Guy; Arnaud, Sylvie; Menk, Roland (Virchows Archiv A Pathological Anatomy and Histology, 1982)
Study of two Paleo-Eskimo skulls found in a necropolis on St-Lawrence Island (Alaska), including radiography and histological examination, revealed the following features. One of the skulls showed a perforation with remodelled borders, considered to be due to trauma and secondary infection. The other showed areas of osteolysis characteristic of a malignant tumor (probably carcinomatous metastasis rather than myeloma). These cases illustrate the advantage of using various methods of investigating bone pathology, particularly microradiography, in skeleton paleopathology.